EPISTEMOLOGY OF CRIMINAL ACTIVITIES IN ZANGON KATAF LOCAL GOVERNMENT AREA, KADUNA STATE, NIGERIA AND INTELLIGENCE-LED POLICE DISCOURSE (Journal of Contemporary Issues in Accounting, 2022)
The study investigated the epistemology of criminal activities in Zangon Kataf Local Government Area, Kaduna State, Nigeria and Intelligence-Led policing discourse. In Nigeria today, criminality is increasingly worrisome, despite the efforts of government and non-governmental organizations to wipe it out. The specific objectives of this study include examining the role of the Nigeria Police in the administration of justice, to identify the inadequacies of the Police in the discharge of their functions and to proffer practical solutions for combating crimes in Nigeria. The significance of this study will help the Nigeria Police Force (NPF) to find a lasting solution to the challenges facing it in its role of combating crimes in Nigeria. Moreover, this study will be of immense benefit to the citizens of Nigeria at large as it will help them to freely speak against crime without fear or bias. Classical Theory of crime was used for this study. The researcher found out that some causes of crime are unemployment, environmental factors, genetic factors, social factors etc. Hence, the researcher recommended that clearly defined goals, results-oriented tactics and strategies, effective intelligence, active collaboration with necessary security agencies and information sharing will assist in the Police in fighting crime.
Keywords: Intelligence-Led Policing; Nigeria Police Force; Criminal Activities